Produktivitetseffekter av flerträdshantering - Rönnqvist, Andreas (2011)
The main purpose of this study is to investigate the productivity effects of multiple tree handling in thinnings. Other important elements have been to investigate in which extent multi-tree handling is used in stands with different stem volumes and the impact of collecting partially delimbed fuelwood assortments has on harvesting performance. The study is based on data from thinnings in Sydved and contractors' operating activities. Collection and compilation of operating schedules, number of stems and surveyed volumes from several contractors and a large number of executed orders underlying the results. Multiple tree handling is used to a much greater extent at lower average stem volumes. Prediction models for productivity of the multiple-tree handling harvesters in the study differ from the productivity models for single-tree handling. In the model developed in this study productivity is not as dependent of stem volume as reference models. Productivity varies greatly between different machines and drivers, which in itself can be a basis to approach the training of drivers. Collection of fuelwood assortments that only needs to be partially delimbed have a certain positive impact on both the proportion of multi managed trees and productivity.